PENGEMBANGAN SUBJECT SPECIFIC PEDAGOGY BERBASIS MODEL PROJECT BASED LEARNING (PjBL) BERBANTUAN SIMULATION BASED LABORATORY (PhET) UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA - Muchairah Haji Hasan; Suparwoto Suparwoto; Moh Toifur (Universitas Halu Oleo, 2022)
This study aims to develop and validate subject-specific pedagogy (SSP) based on PjBL to be suitable for class XI physics learning. This type of research is included in R & D (Research & Development) research using the 4D method: define, design, develop, and disseminate. The results of the product development analysis obtained: (1) The results of the development validation show the teachers' book 3.64 (very valid) Percentage Agreement (PA) of 5.75% (reliable), LKPD 3.55 (very valid) Percentage Agreement (PA) 97, 32% (reliable), Syllabus, 3.62 (very valid) Percentage Agreement (PA) 93.67% (reliable), RPP 3.65 (very valid) Percentage Agreement (PA) 94.93% (reliable), and learning independence 3.56 (very valid) Percentage Agreement (PA) 93.98% suitable for use in learning physics, (2) SSP in increasing learning independence includes: self-confidence, initiative, responsibility, motivation, and discipline.